BMI and weight changes and risk of obesity-related cancers: a pooled European cohort study. (30th September 2019) - Bjørge, Tone; Häggström, Christel; Ghaderi, Sara; Nagel, Gabriele; Manjer, Jonas; Tretli, Steinar; Ulmer, Hanno; Harlid, Sophia; Rosendahl, Ann H; Lang, Alois; Stattin, Pär; Stocks, Tanja; et al.
Abstract: Background: Obesity is an established risk factor for several cancers. Adult weight gain has been associated with increased cancer risk, but studies on timing and duration of adult weight gain are relatively scarce. We examined the impact of BMI (body mass index) and weight changes over time, as well as the timing and duration of excess weight, on obesity- and non-obesity-related cancers. Methods: We pooled health data from six European cohorts and included 221 274 individuals with two or more height and weight measurements during 1972–2014. Several BMI and weight measures were constructed. Cancer cases were identified through linkage with national cancer registries. Hazard ratios (HRs) of cancer with 95% confidence intervals (CIs) were derived from time-dependent Cox-regression models. Results: During follow-up, 27 881 cancer cases were diagnosed; 9761 were obesity-related. The HR of all obesity-related cancers increased with increasing BMI at first and last measurement, maximum BMI and longer duration of overweight (men only) and obesity. Participants who were overweight before age 40 years had an HR of obesity-related cancers of 1.16 (95% CI 1.02, 1.32) and 1.15 (95% CI 1.04, 1.27) in men and women, respectively, compared with those who were not overweight. The risk increase was particularly high for endometrial (70%), male renal-cell (58%) and male colon cancer (29%). No positive associations were seen for cancers not regarded as obesity-related. Conclusions: Adult weight gain was associated with increased risk of several major cancers. The degree, timing and duration of overweight and obesity also seemed to be important. Preventing weight gain may reduce the cancer risk.